2018
DOI: 10.3390/molecules23040807
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose-Induced Cardiomyocyte Death May Be Linked to Unbalanced Branched-Chain Amino Acids and Energy Metabolism

Abstract: High glucose-induced cardiomyocyte death is a common symptom in advanced-stage diabetic patients, while its metabolic mechanism is still poorly understood. The aim of this study was to explore metabolic changes in high glucose-induced cardiomyocytes and the heart of streptozotocin-induced diabetic rats by 1H-NMR-based metabolomics. We found that high glucose can promote cardiomyocyte death both in vitro and in vivo studies. Metabolomic results show that several metabolites exhibited inconsistent variations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 65 publications
0
16
1
Order By: Relevance
“…Creatine is an important indicator for maintaining energy homeostasis, protecting oxidative damage and improving health and survival [ 25 , 26 ]. Creatine can increase creatine phosphate reserves, which can provide energy, protect mitochondria, and reduce cardiomyocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Creatine is an important indicator for maintaining energy homeostasis, protecting oxidative damage and improving health and survival [ 25 , 26 ]. Creatine can increase creatine phosphate reserves, which can provide energy, protect mitochondria, and reduce cardiomyocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia (HG) has been shown to have different damaging effects on cardiomyocyte (CM) function and survival. Exposure to high glucose environment induces CM death both in vitro and in vivo in different animal models of disease including ischaemic 62–65 and non‐ischaemic ones 66–69 . Lower levels of adenosine triphosphate (ATP), adenosine monophosphate (AMP), fumarate, succinate, aspartate and creatinine, alongside increased branched‐chain amino acids content in CM exposed to HG favour their apoptosis 69 .…”
Section: Hyperglycaemiamentioning
confidence: 99%
“…[66][67][68][69] Lower levels of adenosine triphosphate (ATP), adenosine monophosphate (AMP), fumarate, succinate, aspartate and creatinine, alongside increased branched-chain amino acids content in CM exposed to HG favour their apoptosis. 69 Similarly, also oxidative stress through its activating effect on cytochrome c-activated caspase-3 pathway can explain the higher rate of apoptosis in CMs exposed to HG conditions. 66 Moreover, HG was shown to affect the contractile function of CMs by impairing intracellular calcium balance and causing ventricular dilatation and systolic disfunction.…”
Section: Basic Science Researchmentioning
confidence: 99%
“…High glucose alone can promote pathological cardiac development by accelerating hypertrophy, promoting ER stress, increasing ROS production, and ultimately leading to apoptosis (Ng et al, 2018;Zhang X. et al, 2018;Shi et al, 2019). When uncoupled from oxidative phosphorylation, glycolysis produces glycolytic intermediates that can accelerate flux through nonanapleurotic pathways, such as the pentose phosphate pathway (PPP), hexosamine biosynthetic pathway, or lactate shuttling (Gupte et al, 2006;Gibb et al, 2017).…”
Section: Glucotoxicitymentioning
confidence: 99%
“…Li and colleagues recently demonstrated that restoring glucose oxidation by inhibiting pyruvate dehydrogenase kinase (PDK) 4, a rate controlling enzyme of glucose oxidation, improved cardiac function, and glucose uptake post-ischemia reperfusion injury (Li et al, 2017a). Increased glucose exposure over long periods reduces BCAA catabolism, leading to an accumulation of BCAA and BCAA metabolites (Zhang X. et al, 2018). It is well established that leucine, a BCAA, is a potent activator of the mammalian target of rapamycin (mTOR) signaling pathway (Xu and Brink, 2016).…”
Section: Glucotoxicitymentioning
confidence: 99%